Perovskite solar cell
By introducing an organic sulfonate buried interface modification layer into perovskite solar cells, the problem of interface instability of perovskite solar cells is solved, and the power conversion efficiency and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202323634690.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2033-12-28
AI Technical Summary
The long-term operation stability of perovskite solar cells is mainly due to the intrinsic instability caused by deep energy-level traps at the interface, poor interface contact and energy-level barriers, especially between the electron transport layer and the perovskite absorber layer. There is a large interface energy barrier in the interface, which affects the efficient extraction and transmission of carriers.
Introduce an organic sulfonate buried interface modification layer in perovskite solar cells, and use its rich S=O, -C=O, -NH2 functional groups to deactivate the defects of the electron transport layer and the perovskite absorbing layer to reduce the interface Energy level barrier, improve interface contact, and prepare the interface modification layer by spin coating.
It significantly improves the power conversion efficiency and long-term stability of perovskite solar cells, improves the carrier transmission efficiency, and enhances the thermal stability and humidity stability of the battery.
Smart Images

Figure CN222263523U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of perovskite solar cells, in particular to a perovskite solar cell. Background Art
[0002] Perovskite solar cells (PSCs) are one of the new solar cells with the greatest potential for commercial application due to their advantages such as low cost, high efficiency, and solution processing. They are currently the fastest-growing photovoltaic technology, and their efficiency is comparable to that of single-crystalline silicon solar cells. To date, single-junction PSCs have achieved a record certified efficiency of 26.2%. However, the long-term operational stability of the device remains the main obstacle to its large-scale commercial application. The intrinsic instability caused by deep energy level traps at the interface, poor interface contact, and energy level barriers is the biggest challenge to achieving the long-term stability required for practical deployment.
[0003] A large number of deep energy level defects are inevitably generated during the crystallization and growth process of polycrystalline perovskite films. Studies have found that the defect density at the grain boundaries and interfaces of perovskite films is one to two orders of magnitude higher than the defect density inside the grains. These deep energy level defects can cause serious carrier non-radiative recombination losses. In perovskite solar cells, polar solvent molecules (such as dimethyl sulfoxide and N,N-dimethylformamide) in the perovskite precursor solution can destroy the electron transport layer and general interface materials, resulting in unsatisfactory interface contact. In addition, there is a large interface energy barrier between the material of the electron transport layer and the high-efficiency perovskite component, which is not conducive to the efficient extraction and transmission of carriers, resulting in interface charge accumulation and interface carrier non-radiative recombination losses, reducing the photovoltaic performance of the battery. Therefore, it is necessary to develop effective interface molecules to passivate buried interface defects and improve interface contact and band alignment to further improve the photovoltaic performance of perovskite solar cells. Utility Model Content
[0004] In view of this, the main purpose of the present invention is to provide a perovskite solar cell.
[0005] To achieve the above objectives, the first aspect of the utility model provides a perovskite solar cell, which comprises an electron transport layer and a perovskite light absorbing layer, wherein an organic sulfonate buried interface modification layer is provided between the electron transport layer and the perovskite light absorbing layer.
[0006] In some embodiments of the present invention, the organic sulfonate buried interface modification layer is an L-glutamate dibenzyl p-toluenesulfonate buried interface modification layer, a glycine benzyl p-toluenesulfonate buried interface modification layer, or an L-alanine benzyl p-toluenesulfonate buried interface modification layer.
[0007] In some embodiments of the present invention, the thickness of the organic sulfonate buried interface modification layer is in the range of 5 nm to 10 nm.
[0008] In some embodiments of the present invention, the electron transport layer includes a metal oxide electron transport layer.
[0009] In some embodiments of the present invention, the metal oxide electron transport layer is a SnO2 electron transport layer, a TiO2 electron transport layer, a ZnO electron transport layer, a BaSnO3 electron transport layer or a CeO2 electron transport layer.
[0010] In some embodiments of the present invention, the thickness range of the electron transport is 80nm to 200nm.
[0011] In some embodiments of the present invention, the perovskite absorption layer is an ABX3 type perovskite light absorption layer.
[0012] In some embodiments of the present invention, the ABX3 type perovskite absorption layer is a FAPbI3 perovskite absorption layer. In some embodiments of the present invention, the thickness of the perovskite absorption layer ranges from 400nm to 600nm.
[0013] In some embodiments of the present invention, the perovskite solar cell comprises from bottom to top at least a conductive substrate, an electron transport layer, the organic sulfonate buried interface modification layer, a perovskite light absorption layer, a hole transport layer and a back electrode.
[0014] The second aspect of the utility model provides a method for preparing the perovskite solar cell as described above, comprising at least the following steps:
[0015] preparing an electron transport layer on the surface of the substrate;
[0016] Dissolving organic sulfonate molecules in an organic solvent to obtain an organic sulfonate molecule solution, wherein the organic sulfonate molecule solution forms the organic sulfonate buried interface modification layer on the surface of the electron transport layer;
[0017] A perovskite light absorbing layer is prepared on the surface of the organic sulfonate buried interface modification layer.
[0018] In some embodiments of the present invention, the concentration of the organic sulfonate molecule solution is 0.01 mg / mL to 5.0 mg / mL;
[0019] And / or, the organic solvent includes at least one of anisole, dichloromethane, chloroform, chlorobenzene, dichlorobenzene, toluene, ethyl acetate, ether or isopropanol.
[0020] In some embodiments of the present invention, the organic sulfonate buried interface modification layer is prepared by spin coating.
[0021] In some embodiments of the present invention, the spin coating speed of the spin coating method is 2500 rpm to 6500 rpm;
[0022] And / or, the spin coating time of the spin coating method is 25s to 50s.
[0023] In some embodiments of the present invention, the method for preparing the perovskite solar cell further comprises the following steps:
[0024] Cleaning conductive substrates;
[0025] preparing a hole transport layer;
[0026] Prepare the back electrode.
[0027] Beneficial effects that can be achieved by the utility model:
[0028] An organic sulfonate buried interface modification layer is provided between the electron transport layer and the perovskite light absorption layer of the perovskite solar cell of the utility model, and the organic sulfonate buried interface modification layer contains organic sulfonate molecules, and the organic sulfonate molecules contain rich S=O, -C=O, -NH2 functional groups, and the above functional groups can passivate the oxygen vacancy defects in the surface interface of the electron transport layer, and can also effectively passivate the uncoordinated Pb, organic cation vacancies, Pb-I anti-position and other defects in the surface interface of the perovskite light absorption layer. In addition, the above organic sulfonate molecules can also reduce the roughness of the electron transport layer, improve the wettability of the film, and improve the interface contact, which is conducive to the growth of the later perovskite crystals, and can increase the grain size of the perovskite film, and better orientation, thereby promoting the transmission of carriers. Further, the above organic sulfonate molecules can also optimize the energy band arrangement between the electron transport layer and the perovskite light absorption layer, reduce the energy level barrier, and significantly improve the power conversion efficiency and long-term stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the utility model or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the utility model. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0030] Figure 1 This is a cross-sectional view of a perovskite solar cell according to an embodiment of the present invention.
[0031] Figure 2The XPS spectra of the electron transport layer of the comparative example without the organic sulfonate buried interface modification layer and the electron transport layer containing the L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer in Example 1;
[0032] Figure 3 FT-IR spectra of the electron transport layer of the comparative example without the organic sulfonate buried interface modification layer and the electron transport layer containing the L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer in Example 1;
[0033] Figure 4 The XPS spectra of the electron transport layer of the comparative example without the organic sulfonate buried interface modification layer and the electron transport layer containing the L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer in Example 1;
[0034] Figure 5 FT-IR spectra of the electron transport layer of the comparative example without the organic sulfonate buried interface modification layer and the electron transport layer containing the L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer in Example 1;
[0035] Figure 6 The figure shows the theoretical calculation results of the chemical interaction between the organic sulfonate molecules and the SnO2 electron transport layer and the FAPbI3 perovskite light absorption layer;
[0036] Figure 7 The current density-voltage curves of the perovskite solar cells in the comparative example and example 1;
[0037] Figure 8 Graph showing the humidity stability test results of the unencapsulated perovskite solar cells in the comparative example and example 1;
[0038] Fig. 9 This is a graph showing the thermal stability test results of the unencapsulated perovskite solar cell in the comparative example and example 1;
[0039] Fig.10 is a current density-voltage curve diagram of the perovskite solar cell in Example 2;
[0040] Fig.11 Graph showing the humidity stability test results of the unencapsulated perovskite solar cells in the comparative example and example 2;
[0041] Fig.12 This is a graph showing the thermal stability test results of the unencapsulated perovskite solar cells in the comparative example and example 2;
[0042] Fig.13 is a current density-voltage curve diagram of the perovskite solar cell in Example 3;
[0043] Fig.14 Graph showing the humidity stability test results of the unencapsulated perovskite solar cells in the comparative example and example 3;
[0044] Fig.15 This is a graph showing the thermal stability test results of the unencapsulated perovskite solar cells in Comparative Example and Example 3.
[0045] The reference numerals are as follows:
[0046] 1 Conductive substrate 2 Electron transport layer 3 Organic sulfonate buried interface modification layer 4 Perovskite light-absorbing layer 5 Hole transport layer 6 Back electrode
[0047] The realization of the purpose, functional features and advantages of the utility model will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0048] It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0050] In the present utility model, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present utility model.
[0051] The utility model provides a perovskite solar cell. The perovskite solar cell comprises an electron transport layer and a perovskite light absorbing layer. An organic sulfonate buried interface modification layer is arranged between the electron transport layer and the perovskite light absorbing layer.
[0052] In the utility model, the organic sulfonate molecules in the organic sulfonate buried interface modification layer belong to existing materials and contain rich S=O, -C=O, -NH2 functional groups. The above functional groups can passivate the oxygen vacancy defects in the surface interface of the electron transport layer, and can also effectively passivate the uncoordinated Pb, organic cation vacancies, Pb-I anti-sites and other defects in the surface interface of the perovskite light absorption layer. In addition, the above-mentioned organic sulfonate molecules can also reduce the roughness of the electron transport layer, improve the wettability of the film, and improve the interface contact, which is conducive to the growth of the later perovskite crystals, and can increase the grain size of the perovskite film, and better orient it, thereby promoting the transmission of carriers. Furthermore, the above-mentioned organic sulfonate molecules can also optimize the energy band arrangement between the electron transport layer and the perovskite light absorption layer, reduce the energy level barrier, and significantly improve the power conversion efficiency and long-term stability of the perovskite solar cell.
[0053] In some embodiments, the organic sulfonate buried interface modification layer is an L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer, a glycine benzyl p-toluenesulfonate buried interface modification layer, or an L-alanine benzyl p-toluenesulfonate buried interface modification layer, wherein L-glutamic acid dibenzyl p-toluenesulfonate, glycine benzyl p-toluenesulfonate, and L-alanine benzyl p-toluenesulfonate are all existing materials, and their structures are shown below:
[0054]
[0055] In the above structural formula, M1 refers to L-glutamic acid dibenzyl p-toluenesulfonate, M2 refers to glycine benzyl p-toluenesulfonate, and M3 refers to L-alanine benzyl p-toluenesulfonate.
[0056] The L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer, the glycine benzyl p-toluenesulfonate buried interface modification layer or the L-alanine benzyl p-toluenesulfonate buried interface modification layer all contain abundant S=O, -C=O, -NH2, and have many active sites, which can not only effectively passivate the oxygen vacancy defects in the surface interface of the electron transport layer, but also effectively passivate the uncoordinated Pb, organic cation vacancies, Pb-I antisites and other defects in the surface interface of the perovskite.
[0057] In some embodiments, the thickness of the organic sulfonate buried interface modification layer is in the range of 5 nm to 10 nm, and can be any value in the range of 5 nm to 10 nm, such as 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc. This is beneficial to improving the passivation defect of the organic sulfonate buried interface modification layer, improving interface contact, and optimizing the ability of energy level matching.
[0058] In some embodiments, the electron transport layer comprises a metal oxide electron transport layer.
[0059] In some embodiments, the metal oxide electron transport layer is a SnO2 electron transport layer, a TiO2 electron transport layer, a ZnO electron transport layer, a BaSnO3 electron transport layer or a CeO2 electron transport layer. The above metal oxide electron transport layer is a common type of electron transport layer in normal perovskite solar cells.
[0060] However, there is usually a large interface energy barrier between the metal oxide electron transport layer and the perovskite light absorption layer, which is not conducive to the efficient extraction and transport of carriers, and will lead to interface charge accumulation and interface carrier non-radiative recombination losses, which will reduce the photovoltaic performance of the battery.
[0061] The utility model can alleviate the above problems by setting an organic sulfonate buried interface modification layer between the metal oxide electron transport layer and the perovskite light absorption layer. The rich S=O, -C=O, -NH2 in the organic sulfonate buried interface modification layer can optimize the energy band arrangement between the metal oxide electron transport layer and the perovskite light absorption layer, reduce the energy level barrier, promote the transmission of carriers, and also reduce the roughness of the metal oxide electron transport layer, improve the wettability of the film, improve the interface contact, and facilitate the deposition and growth of perovskite crystals in the later stage, increase the grain size of the perovskite film, and better the orientation, thereby further promoting the transmission of carriers, thereby significantly improving the power conversion efficiency and long-term stability of the perovskite solar cell. In addition, S=O, -C=O, -NH2 in the organic sulfonate buried interface modification layer can react chemically with the metal elements in the metal oxide electron transport layer, fill the oxygen vacancies in the metal oxide lattice in the metal oxide electron transport layer, and effectively reduce the defect density of the metal oxide electron transport layer, which is beneficial to increase the carrier concentration and reduce the probability of electron capture, thereby improving the thermal stability of the perovskite solar cell, and also avoiding the rapid recombination of the perovskite solar cell after the separation of the excitons, which is beneficial to the charge transfer of the perovskite solar cell and improves the short-circuit current density of the battery. Further, S=O, -C=O, -NH2 in the organic sulfonate buried interface modification layer and the metal ions in the metal oxide electron transport layer can form an ionic bond with a stronger bond energy than metal-oxygen, so that the metal oxide electron transport layer tends to a good stoichiometric ratio, which can effectively improve the structure and thermal stability of the perovskite solar cell.
[0062] In some embodiments, the thickness range of the electron transport layer is 80nm to 200nm, which can be any value in the range of 80nm to 200nm, such as 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 130nm, 150nm, 180nm, 200nm, etc., which is beneficial to improve the electron transmission efficiency and block holes.
[0063] In some embodiments, the perovskite light absorbing layer is an ABX3 type perovskite light absorbing layer, wherein A is CH3NH 3+ 、CH(NH2) 2+ , Cs + or Rb + ; and / or, B is Pb 2+ Sn 2+ Or Ge 2+ ; and / or, X is Cl - Br - or I - In one embodiment, the ABX3 type perovskite light absorption layer is a FAPbI3 perovskite light absorption layer. As a common perovskite light absorption layer in an orthogonal perovskite solar cell, the ABX3 type perovskite light absorption layer is prone to have a large interface energy barrier with the electron transport layer, especially the metal oxide electron transport layer, which is not conducive to the efficient extraction and transmission of carriers, and is prone to cause interface charge accumulation and interface carrier non-radiative recombination loss, thereby reducing the photovoltaic performance of the cell.
[0064] The utility model sets a buried interface light-absorbing layer between the ABX3 type perovskite light-absorbing layer and the electron transport layer, which can well alleviate the above problems. Specifically, the abundant S=O, -C=O, -NH2 in the organic sulfonate molecules in the organic sulfonate buried interface modification layer can optimize the energy band arrangement between the electron transport layer and the ABX3 type perovskite light-absorbing layer, reduce the energy level barrier, promote the transmission of carriers, and also reduce the roughness of the electron transport layer, improve the wettability of the film, and improve the interface contact, which is conducive to the deposition and growth of the ABX3 perovskite crystals in the later stage, increase the grain size of the ABX3 type perovskite film, and have a better orientation, thereby further promoting the transmission of carriers, thereby significantly improving the power conversion efficiency and long-term stability of the perovskite solar cell. In addition, S=O, -C=O, and -NH2 in the organic sulfonate buried interface modification layer can chemically react with the uncoordinated Pb in the ABX3 type perovskite light-absorbing layer to achieve defect passivation of the perovskite light-absorbing layer, and can also passivate deep energy level defects such as FA vacancies and Pb-I antisites. Therefore, the above-mentioned organic sulfonate molecules can chemically bridge between the electron transport layer and the perovskite light-absorbing layer.
[0065] In some embodiments, the thickness of the perovskite light absorbing layer ranges from 400nm to 600nm, and can be any value in the range of 400nm to 600nm, such as 400nm, 420nm, 450nm, 460nm, 480nm, 500nm, 520nm, 530nm, 540nm, 550nm, 580nm, 600nm, etc., so that the perovskite light absorbing layer can absorb sunlight more fully.
[0066] In addition to the above-mentioned electron transport layer, organic sulfonate buried interface modification layer and perovskite light absorption layer, the perovskite solar cell of the utility model also includes some common functional layers of perovskite solar cells in the related field, including but not limited to a conductive substrate, a hole transport layer and a back electrode.
[0067] In some embodiments, the perovskite solar cell comprises at least a conductive substrate, an electron transport layer, an organic sulfonate buried interface modification layer of the present invention, a perovskite light absorption layer, a hole transport layer and a back electrode from bottom to top. The perovskite solar cell of this embodiment is a normal perovskite solar cell.
[0068] It can be understood that in this embodiment, the conductive substrate, the electron transport layer, the organic sulfonate buried interface modification layer, the perovskite light absorption layer, the hole transport layer and the back electrode are arranged in sequence, and the organic sulfonate buried interface modification layer is provided between the electron transport layer and the perovskite light absorption layer. Other functional layers commonly used in the art can also be prepared between the conductive substrate and the electron transport layer, between the perovskite light absorption layer and the hole transport layer, and between the hole transport layer and the back electrode. For example, a passivation layer is prepared between the perovskite light absorption layer and the hole transport layer. There is no limitation here and it can be designed according to actual needs.
[0069] In some embodiments, the perovskite cell of the present invention includes a conductive substrate, and the thickness of the conductive substrate ranges from 100nm to 200nm, which can be any value in the range of 100nm to 200nm, such as 100nm, 110nm, 120nm, 130nm, 140nm, 50nm, 160nm, 170nm, 180nm, 190nm, 200nm, etc.
[0070] In some embodiments, the perovskite battery of the present invention includes a hole transport layer, and the thickness of the hole transport layer ranges from 80nm to 200nm, which can be any value in the range of 80nm to 200nm, such as 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 80nm, 190nm, 200nm, etc.
[0071] In some embodiments, the perovskite cell of the present invention includes a back electrode having a thickness ranging from 60 nm to 150 nm, which can be any value within the range of 60 nm to 150 nm, such as 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, etc.
[0072] The utility model also provides a method for preparing a perovskite solar cell, which comprises at least the following steps:
[0073] preparing an electron transport layer on the surface of the substrate;
[0074] Dissolving organic sulfonate molecules in an organic solvent to obtain an organic sulfonate molecule solution, wherein the organic sulfonate molecule solution forms the organic sulfonate buried interface modification layer on the surface of the electron transport layer;
[0075] A perovskite light absorbing layer is prepared on the surface of the organic sulfonate buried interface modification layer.
[0076] It is understandable that the preparation of the above-mentioned electron transport layer, organic sulfonate buried interface modification layer and perovskite light absorption layer is only part of the process steps in the preparation of perovskite solar cells of the utility model, and can also include the preparation of other functional layers to prepare a complete perovskite solar cell device, and the above-mentioned other functional layers include but are not limited to conductive substrates, hole transport layers, back electrodes and some modification layers such as passivation layers, which can be prepared by methods familiar to those skilled in the art. For example, in some embodiments, the preparation method of perovskite solar cells also includes the following steps: cleaning the conductive substrate; preparing the hole transport layer; preparing the back electrode.
[0077] In the utility model, an electron transport layer is prepared on the surface of a substrate, the substrate comprises a conductive substrate, and the electron transport layer is prepared on the surface of the conductive substrate.
[0078] In some embodiments, the conductive substrate includes ITO or FTO.
[0079] In some embodiments, the conductive substrate is cleaned with detergent, deionized water, acetone, and anhydrous ethanol in sequence, ultrasonically cleaned, blown dry with nitrogen, and then treated with ultraviolet ozone for 15 minutes, and cooled for later use.
[0080] In this embodiment, the substrate may also be a composite layer of a conductive substrate and a modified layer, and the electron transport layer is prepared on the surface of the conductive substrate.
[0081] A modification layer may also be prepared on the surface of the conductive substrate. The modification layer includes a functional layer for modifying the conductive substrate and the electron transport layer that is well known to those skilled in the art.
[0082] In some embodiments, the material for preparing the electron transport layer includes a metal oxide, and the metal oxide includes at least one of SnO2, TiO2, ZnO, BaSnO3 or CeO2, thereby preparing a metal oxide electron transport layer. It should be noted that the metal oxide of the electron transport layer material can be prepared to form an electron transport precursor solution by using commonly used technical means in the art, and the electron transport precursor solution forms an electron transport layer on the surface of the substrate.
[0083] In some embodiments, the metal oxides mentioned above can be dispersed in deionized water to form an electron transport precursor solution.
[0084] In some embodiments, the method of preparing the electron transport layer comprises spin coating.
[0085] In some embodiments, the electron transport layer is prepared by spin coating, and the spin coating conditions are as follows: the spin coating speed is 2500rpm~3500rpm, and can be 2500rpm, 2800rpm, 3000rpm, 3200rpm, 3300rpm, 3500rpm, and any value in the range of 2500rpm~3500rpm; and / or, the spin coating time is 25s~40s, and can be 25s, 28s, 30s, 35s, 38s, 40s, and any value in the range of 25s~40s.
[0086] In some embodiments, the electron transport layer is annealed, and the annealing conditions are as follows: annealing at 120°C to 180°C for 20 min to 35 min, the annealing temperature can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and any value in the range of 120°C to 180°C, and the annealing time can be 20 min, 25 min, 30 min, 35 min, and any value in the range of 20 min to 35 min.
[0087] In some embodiments, the annealed electron transport layer is cleaned to remove residues and impurities on the surface of the electron transport layer, thereby strengthening the contact and bonding between the electron transport layer and the organic sulfonate buried interface modification layer, promoting a chemical reaction between the active groups in the organic sulfonate molecules in the organic sulfonate buried interface modification layer and the electron transport layer, passivating oxygen vacancies in the electron transport layer, and enhancing carrier transport.
[0088] In some embodiments, the method of cleaning the electron transport layer includes ultraviolet ozone irradiation treatment or plasma treatment.
[0089] In the related art, the prepared electron transport layer usually has defects such as oxygen vacancies, and the perovskite light-absorbing layer is directly prepared on the surface of the electron transport layer, especially the metal oxide electron transport layer. There is easily a large interface energy barrier between the electron transport layer and the perovskite components in the perovskite light-absorbing layer, which is not conducive to the efficient extraction and transmission of carriers, and will lead to interface charge accumulation and interface carrier non-radiative recombination losses, which will reduce the photovoltaic performance of the battery.
[0090] Therefore, the utility model prepares an organic sulfonate buried interface modification layer between the electron transport layer and the perovskite light absorbing layer, which can solve the above problems well. The rich S=O, -C=O, -NH2 in the organic sulfonate molecules in the organic sulfonate buried interface modification layer can optimize the energy band arrangement between the electron transport layer and the perovskite light absorbing layer, reduce the energy level barrier, promote the transmission of carriers, and also reduce the roughness of the electron transport layer, improve the wettability of the film, improve the interface contact, and facilitate the deposition and growth of perovskite crystals in the later stage, increase the grain size of the perovskite film, and better the orientation, thereby further promoting the transmission of carriers, thereby significantly improving the power conversion efficiency and long-term stability of the perovskite solar cell. In addition, S=O, -C=O, and -NH2 in the organic sulfonate molecules can react chemically with the metal elements in the electron transport layer to fill the oxygen vacancies in the lattice of the electron transport layer material, which can effectively reduce the defect density of the electron transport layer, which is beneficial to increase the carrier concentration and reduce the probability of electron capture, thereby improving the thermal stability of the perovskite solar cell. At the same time, it can also avoid the rapid recombination of the perovskite solar cell after the separation of the excitons, which is beneficial to the charge transfer of the perovskite solar cell and improve the short-circuit current density of the battery.
[0091] In some embodiments, the concentration of the organic sulfonate molecule solution is 0.01 mg / mL to 5.0 mg / mL, for example, 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1.0 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.7 mg / mL, 1.9 mg / mL, 2 .0mg / mL, 2.1mg / mL, 2.3mg / mL, 2.5mg / mL, 2.8mg / mL, 2.9mg / mL, 3.0mg / mL, 3.2mg / mL, 3.5mg / mL, 3.8mg / mL, 3.9mg / mL, 4.0mg / mL, 4.1mg / mL, 4.3mg / mL, 4.5mg / mL, 4.8mg / mL, 5.0mg / mL, etc. Any concentration value in the range of 0.01mg / mL to 5.0mg / mL. Under the above concentration range conditions, the organic sulfonate molecules can provide abundant active sites, which can effectively passivate a large number of oxygen vacancy defects in the surface interface of the electron transport layer, and can also effectively passivate a large number of uncoordinated Pb, organic cation vacancies, Pb-I antisites and other defects in the surface interface of the perovskite.
[0092] In some embodiments, the organic sulfonate buried interface modification layer can be prepared by spin coating.
[0093] In some embodiments, the organic sulfonate buried interface modification layer is prepared by spin coating, and the spin coating speed is 2500rpm~6500rpm, which can be 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm, 5000rpm, 6000rpm, 6500rpm, and any value in the range of 2500rpm~6500rpm.
[0094] In some embodiments, the organic sulfonate buried interface modification layer is prepared by spin coating, and the spin coating time is 25s to 50s, which can be 25s, 28s, 30s, 32s, 35s, 38s, 40s, 43s, 45s, 48s, 50s, and any value in the range of 25s to 50s.
[0095] Under the above spin coating speed and spin coating time conditions, it is beneficial to promote the organic sulfonate molecular solution to form a uniform organic sulfonate buried interface modification layer on the surface of the electron transport layer, thereby improving the passivation effect of the organic sulfonate buried interface modification layer on the oxygen vacancy defects of the electron transport layer.
[0096] In some embodiments, the organic solvent includes at least one of anisole, dichloromethane, chloroform, chlorobenzene, dichlorobenzene, toluene, ethyl acetate, ether, or isopropanol. The above organic solvents can dissolve the organic sulfonate molecules to obtain a uniform organic sulfonate molecule solution, and form a uniform organic sulfonate buried interface modification layer on the surface of the electron transport layer.
[0097] After completing the above-mentioned organic sulfonate buried interface modification layer, the utility model prepares a perovskite light absorption layer on the surface of the organic sulfonate buried interface modification layer. The organic sulfonate molecules in the organic sulfonate buried interface modification layer reduce the roughness of the electron transport layer, improve the wettability of the film, can improve the interface contact, is beneficial to the growth of perovskite crystals, can increase the grain size of the perovskite film, and have a better orientation, thereby promoting the transmission of carriers.
[0098] In some embodiments, the perovskite absorption layer is an ABX3 type perovskite absorption layer, wherein A comprises CH3NH 3+ 、CH(NH2) 2+ , Cs + or Rb + At least one of; and / or, B includes Pb 2+ Sn 2+ Or Ge 2+ At least one of; and / or, X includes Cl - Br - or I -At least one of them. ABX3 belongs to existing materials and is a commonly used material for preparing the perovskite light-absorbing layer of the normal perovskite solar cell. It is easy to have a large interface energy barrier between the electron transport layer material, especially the metal oxide electron transport layer material, which is not conducive to the efficient extraction and transmission of carriers, and it is easy to cause interface charge accumulation and interface carrier non-radiative recombination loss, reducing the photovoltaic performance of the battery. The buried interface light-absorbing layer of the utility model is prepared between the ABX3 type perovskite light-absorbing layer and the electron transport layer, which can solve the above problems well. Specifically, the rich S=O, -C=O, and -NH2 in the organic sulfonate molecules in the organic sulfonate buried interface modification layer can optimize the energy band arrangement between the electron transport layer and the perovskite light-absorbing layer, reduce the energy level barrier, and promote the transmission of carriers. Moreover, it can also reduce the roughness of the electron transport layer, improve the wettability of the film, and improve the interface contact, which is conducive to the deposition and growth of the perovskite crystals in the later stage, increase the grain size of the perovskite film, and have a better orientation, thereby further promoting the transmission of carriers, thereby significantly improving the power conversion efficiency and long-term stability of the perovskite solar cell. In addition, S=O, -C=O, and -NH2 in the organic sulfonate molecules can react chemically with the uncoordinated Pb in the perovskite light-absorbing layer to passivate the defects of the perovskite light-absorbing layer, and can also passivate deep energy level defects such as FA vacancies and Pb-I antisites. Therefore, the above-mentioned organic sulfonate molecules can chemically bridge the electron transport layer and the perovskite light-absorbing layer.
[0099] After completing the preparation of the above-mentioned perovskite light-absorbing layer, other functional layers required to form a complete perovskite solar cell device such as a hole transport layer and a back electrode can be further prepared.
[0100] In some embodiments, the method for preparing a perovskite solar cell of the present invention further includes preparing a hole transport layer.
[0101] In some embodiments, a hole transport layer is prepared on the surface of the perovskite light absorbing layer.
[0102] In some embodiments, the material for preparing the hole transport layer includes at least one of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(3-hexylthiophene-2,5-diyl), cuprous thiocyanate, cuprous iodide or nickel oxide.
[0103] The utility model does not limit the specific method for preparing the hole transport layer, and the commonly used methods in the art can be selected.
[0104] In some embodiments, the hole transport layer is prepared by spin coating, wherein the hole transport layer material is dissolved in an organic solvent to obtain a hole transport precursor solution, and then the hole transport precursor solution is spin coated on the surface of the substrate to form the hole transport layer. For example, the hole transport layer is spin coated on the surface of the perovskite light absorption layer to form the hole transport layer.
[0105] In this embodiment, the organic solvent for dissolving the hole transport layer material includes chlorobenzene and acetonitrile. Chlorobenzene can be used to dissolve 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), and then TBP (tributylphosphine) and Li-TFSI (lithium bistrifluoromethanesulfonyl imide) dissolved in acetonitrile are added to obtain a hole transport precursor solution.
[0106] In some embodiments, the method for preparing a perovskite solar cell of the present invention further includes preparing a hollow scar electrode.
[0107] In some embodiments, a back electrode is formed on the surface of the hole transport layer.
[0108] In this embodiment, the back electrode can be prepared by selecting materials and methods well known to those skilled in the art.
[0109] In some embodiments, the material used to make the back electrode includes any one of Au, Ag, or a low-temperature carbon electrode.
[0110] In some embodiments, the back electrode can be prepared on the surface of the substrate by thermal evaporation. For example, the back electrode can be prepared by thermal evaporation on the surface of the hole transport layer.
[0111] In some embodiments, the preparation method of the perovskite solar cell of the present invention further includes the preparation of a modification layer, which includes but is not limited to a passivation layer. For example, a passivation layer can be prepared on the surface of the perovskite light-absorbing layer, and then a hole transport layer can be prepared on the surface of the passivation layer. The present invention does not limit the preparation of the above-mentioned functional layers, and can be designed according to actual needs.
[0112] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0113] Example 1
[0114] Example 1 prepares an inverted perovskite solar cell containing a buried interface modification layer of L-glutamic acid dibenzyl p-toluenesulfonate, and the specific preparation method is as follows:
[0115] (1) The ITO conductive substrate was cleaned with detergent, deionized water, acetone, and anhydrous ethanol in sequence, then dried with nitrogen, treated with ultraviolet ozone for 15 minutes, and cooled for later use;
[0116] (2) adding 750 μL of deionized water to 250 μL of a 15% SnO2 nanoparticle dispersion, filtering through a 0.22 μm PVDF, taking 40 μL and dropping it onto the ITO conductive substrate treated in step (1), spin coating at 3000 rpm for 30 seconds, and then annealing at 150°C for 30 minutes to obtain an electron transport layer, and then irradiating the electron transport layer with ultraviolet ozone for 15 minutes to obtain an electron transport layer with a thickness of 80 nm to 200 nm;
[0117] (3) dissolving 0.5 mg of L-glutamic acid dibenzyl p-toluenesulfonate in 1 mL of isopropanol to prepare a 0.5 mg / mL L-glutamic acid dibenzyl p-toluenesulfonate solution, taking 30 μL of the solution and dropping it onto the electron transport layer in step (2), spin coating at 5000 rpm for 33 s, and annealing at 100° C. for 10 min to obtain a L-glutamic acid dibenzyl p-toluenesulfonate buried interface modification layer with a thickness of 5 nm to 10 nm;
[0118] (4) FAI (248.16 mg), CsI (19.73 mg), RbI (6.58 mg), PbI2 (682.73 mg), PbBr2 (8.53 mg), PbCl2 (12.74 mg) and MACl (35 mg) were dissolved in a mixed solvent of DMF and DMSO (the volume ratio of DMF to DMSO was 4:1), and the solution was shaken for 10 min to obtain a perovskite precursor solution with a concentration of 1.55 mol / L. After filtering through 0.22 μm PTFE, 40 μL was added dropwise onto the electron transport layer in step (2), and the solution was spin-coated at 4000 rpm for 30 s. 80 μL of chlorobenzene was added dropwise 15 to 16 seconds before the end of spin coating, and then annealed at 130° C. for 30 min to obtain a perovskite light absorbing layer with a thickness of 400 nm to 600 nm.
[0119] (5) Dissolve 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, add 29 μL of TBP and 18 μL of Li-TFSI (concentration of 520 mg / mL, solvent is anhydrous acetonitrile), mix well, take 30 μL and drop it onto the interface modification layer in step (4), spin-coat at a speed of 3000 rpm for 30 seconds to obtain a hole transport layer with a thickness of 80 nm to 200 nm;
[0120] (6) In high vacuum (10 -4At 250 Å / s (200 Å / s), an Au electrode with a thickness of 60 nm to 150 nm is deposited on the hole transport layer in step (5) by thermal evaporation.
[0121] The structural formula of L-glutamic acid dibenzyl ester p-toluenesulfonate is as follows:
[0122]
[0123] Example 2
[0124] Example A perovskite solar cell was prepared by referring to the preparation method of Example 1, except that 0.5 mg of L-glutamic acid dibenzyl p-toluenesulfonate was replaced with 0.5 mg of glycine benzyl p-toluenesulfonate to prepare a glycine benzyl p-toluenesulfonate buried interface modification layer with a thickness of 5 nm to 10 nm.
[0125] The structural formula of glycine benzyl ester p-toluenesulfonate is shown below:
[0126]
[0127] Example 3
[0128] Example 3 A perovskite solar cell was prepared by referring to the preparation method of Example 1, except that 0.5 mg of L-glutamate dibenzyl p-toluenesulfonate was replaced with 0.5 mg of L-alanine benzyl p-toluenesulfonate to prepare a L-alanine benzyl p-toluenesulfonate buried interface modification layer with a thickness of 5 nm to 10 nm.
[0129] The structural formula of L-alanine benzyl ester p-toluenesulfonate is shown below:
[0130]
[0131] The structure of the perovskite solar cell prepared in the above-mentioned embodiments 1 to 3 is as follows: Figure 1 As shown, from bottom to top are a conductive substrate 1, an electron transport layer 2, an organic sulfonate buried interface modification layer 3, a perovskite light absorption layer 4, a hole transport layer 5, and a back electrode 6.
[0132] Comparative Example
[0133] Comparative Example The preparation method of Example 1 is referred to, except that the perovskite light absorbing layer is directly prepared on the surface of the electron transport layer, and the organic sulfonate buried interface modification layer is not prepared.
[0134] The structure of the perovskite solar cell prepared in the comparative example is, from bottom to top, a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a back electrode.
[0135] Performance Test 1
[0136] The perovskite solar cells of Example 1 and Comparative Example were characterized by XPS spectrometer and FT-IR spectrometer. Figures 2 to 6 .
[0137] Figure 2 The XPS spectra of Sn 3d and O1s of the electron transport layer without interface modification layer in the comparative example and the electron transport layer coated with L-glutamic acid dibenzyl p-toluenesulfonate to modify the buried interface in Example 1 are shown. By comparison, it can be seen that after the buried interface is modified by coating with L-glutamic acid dibenzyl p-toluenesulfonate, the peak position of the Sn 3d element in the electron transport layer is shifted, and in the XPS spectrum of O1s, the absorption peak attributed to the oxygen vacancy becomes smaller, while the absorption peak attributed to the oxygen lattice becomes larger, indicating that S=O and C=O react chemically with Sn, and the L-glutamic acid dibenzyl p-toluenesulfonate molecules in the buried interface modified by L-glutamic acid dibenzyl p-toluenesulfonate passivate the oxygen vacancy defects in the electron transport layer.
[0138] Figure 3 The FT-IR spectra of the electron transport layer without interface modification layer in the comparative example and the electron transport layer coated with L-glutamic acid dibenzyl p-toluenesulfonate to modify the buried interface in Example 1 are shown. By comparison, it can be seen that after the buried interface is modified by coating with L-glutamic acid dibenzyl p-toluenesulfonate, the peak positions of S=O and C=O are shifted, which once again shows that both S=O and C=O can chemically react with Sn to passivate the oxygen vacancy defects in the electron transport layer.
[0139] Figure 4 The Pb 4f ( Figure 4 a), O 1s( Figure 4 b) and N1s( Figure 4 By comparing the XPS spectra of (c) in Figure 1, it can be seen that after the modification of the buried interface modification layer of L-glutamic acid dibenzyl ester p-toluenesulfonate, the absorption peak of the perovskite Pb 4f shifts to the low energy direction, while the absorption peaks of S=O and C=O in the L-glutamic acid dibenzyl ester p-toluenesulfonate molecule shift to the high energy direction, and the absorption peak attributed to Pb…O appears. In addition, the absorption peak attributed to -NH 3+ The absorption peak also shifted, indicating that the L-glutamic acid dibenzyl ester toluenesulfonate molecule can also achieve defect passivation of the perovskite light-absorbing layer by chemically reacting with Pb.
[0140] Figure 5The FT-IR spectra of the perovskite light-absorbing layer without the interface modification layer in the comparative example and the perovskite with the interface modification layer buried with L-glutamic acid dibenzyl p-toluenesulfonate in Example 1 are shown in FIG. 1 . After modification with the interface modification layer buried with L-glutamic acid dibenzyl p-toluenesulfonate, -NH 3+ The peak positions of S=O and C=O have shifted, which again indicates that -NH 3+ , S=O and C=O can all react chemically with Sn.
[0141] Figure 6 This is the theoretical calculation result of the chemical interaction between the L-glutamate dibenzyl p-toluenesulfonate molecules in the L-glutamate dibenzyl p-toluenesulfonate buried interface modification layer and the SnO2 electron transport layer and the FAPbI3 perovskite light absorbing layer in Example 1. The L-glutamate dibenzyl p-toluenesulfonate molecules can passivate the oxygen vacancy defects in the SnO2 layer, and can also passivate deep energy level defects such as uncoordinated Pb, FA vacancies and Pb-I antisites in the perovskite layer. Therefore, the L-glutamate dibenzyl p-toluenesulfonate buried interface modification layer is well chemically bridged with the electron transport layer and the perovskite light absorbing layer.
[0142] Performance Test 2
[0143] The current density-voltage curves of the perovskite solar cells in the comparative example and example 1, example 2, and example 3 are shown in FIG. Figure 7 , Figure 8 , Fig. 9 , and according to Figures 7 to 9 The corresponding photovoltaic parameters are obtained and the results are shown in Table 1.
[0144] Table 1 Photovoltaic parameters of perovskite solar cells in comparative example and examples 1 to 3
[0145]
[0146]
[0147] Depend on Figure 7 As shown in Table 1, the short-circuit current density, open-circuit voltage and fill factor of the perovskite solar cell in Example 1 are significantly improved, and the power conversion efficiency is increased from 21.43% of the comparative example to 23.58%.
[0148] Depend on Figure 8 As can be seen from Table 1, the open circuit voltage of the perovskite solar cell in Example 2 is improved, and the power conversion efficiency is increased from 21.43% of the comparative example to 23.47%.
[0149] Depend on Fig. 9As can be seen from Table 1, the open circuit voltage and fill factor of the perovskite solar cell in Example 3 are improved, and the power conversion efficiency is increased from 21.43% of the comparative example to 23.27%.
[0150] Performance Test 3
[0151] The humidity stability of the perovskite solar cells obtained in the comparative example and examples 1 to 3 was measured, and the results were shown in Table 1. Fig.10 , Fig.11 and Fig.12 .
[0152] Fig.10 1 is a graph showing the humidity stability test results of the unencapsulated perovskite solar cell in the comparative example and example 1. Fig. 9 It can be seen that the unpackaged perovskite solar cell in Example 1 maintains 91.73% of the initial efficiency after aging for 3000 hours under a relative humidity condition of 30% to 40%.
[0153] Fig.11 1 is a graph showing the humidity stability test results of the unencapsulated perovskite solar cell in the comparative example and example 2. Fig.10 It can be seen that the unpackaged perovskite solar cell in Example 2 maintains 91.02% of the initial efficiency after aging for 3000 hours under a relative humidity condition of 30% to 40%.
[0154] Fig.12 Graph showing the humidity stability test results of the unencapsulated perovskite solar cells in the comparative example and example 3. Fig.13 It can be seen that the unpackaged perovskite solar cell in Example 3 maintains 90.86% of the initial efficiency after aging for 3000 hours under a relative humidity condition of 30% to 40%.
[0155] The initial efficiency of the comparative example is only 78.11%.
[0156] Performance Test 4
[0157] The thermal stability of the perovskite solar cells obtained in Examples 1 to 3 and Comparative Example was measured, and the results are shown in Table 1. Fig.13 , Fig.14 and Fig.15 .
[0158] Fig.13 The thermal stability test results of the unencapsulated perovskite solar cell in the comparative example and example 1 are shown in FIG. Fig.12 It can be seen that the unencapsulated perovskite solar cell in Example 1 maintains 83.21% of the initial efficiency after aging for 2000 h in a 65°C environment.
[0159] Fig.14The thermal stability test results of the unencapsulated perovskite solar cell in the comparative example and example 2 are shown in FIG. Fig.13 It can be seen that the unencapsulated perovskite solar cell in Example 2 maintains 83.09% of the initial efficiency after aging for 2000 h in a 65°C environment.
[0160] Fig.15 The thermal stability test results of the unencapsulated perovskite solar cell in the comparative example and example 3 are shown in FIG. Fig.14 It can be seen that the unencapsulated perovskite solar cell in Example 3 maintains 81.77% of the initial efficiency after aging for 2000 h in a 65°C environment.
[0161] The initial efficiency of the comparative example is only 65.23%.
[0162] From performance tests 1 to 4, it can be known that the buried interface modification layer of L-glutamic acid dibenzyl p-toluenesulfonate, the buried interface modification layer of glycine benzyl p-toluenesulfonate, and the buried interface modification layer of L-alanine benzyl p-toluenesulfonate contain abundant S=O, -C=O, and -NH2 functional groups, which can passivate the oxygen vacancy defects in the surface interface of the electron transport layer, and can also effectively passivate the uncoordinated Pb, organic cation vacancies, Pb-I anti-site and other defects in the surface interface of the perovskite light absorption layer. In addition, the above-mentioned organic sulfonate molecules can also reduce the roughness of the electron transport layer, improve the wettability of the film, and improve the interface contact, which is conducive to the growth of the later perovskite crystals, and can increase the grain size of the perovskite film, and have a better orientation, thereby promoting the transmission of carriers. Further, the above-mentioned organic sulfonate molecules can also optimize the energy band arrangement between the electron transport layer and the perovskite light absorption layer, reduce the energy level barrier, and significantly improve the power conversion efficiency and long-term stability of the perovskite solar cell. Specifically, performance test 2 proved that the photovoltaic performance of perovskite solar cells was effectively improved; performance test 3 proved that the humidity stability of perovskite solar cells was effectively improved; and performance test 4 proved that the thermal stability of perovskite solar cells was effectively improved.
[0163] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the specification and drawings of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The perovskite solar cell comprises an electron transport layer and a perovskite light absorption layer, and an organic sulfonate buried interface modification layer is provided between the electron transport layer and the perovskite light absorption layer; The organic sulfonate bottom buried interface modification layer is an L-glutamic acid dibenzyl p-toluenesulfonate bottom buried interface modification layer, a glycine benzyl p-toluenesulfonate bottom buried interface modification layer or an L-alanine benzyl p-toluenesulfonate bottom buried interface modification layer.
2. The perovskite solar cell according to claim 1, characterized in that The thickness of the organic sulfonate buried interface modification layer ranges from 5 nm to 10 nm.
3. The perovskite solar cell according to claim 1, characterized in that The electron transport layer includes a metal oxide electron transport layer.
4. The perovskite solar cell according to claim 3, characterized in that: The metal oxide electron transport layer is a SnO2 electron transport layer, a TiO2 electron transport layer, a ZnO electron transport layer, a BaSnO3 electron transport layer or a CeO2 electron transport layer.
5. The perovskite solar cell according to claim 1, characterized in that: The thickness range of electron transport is 80nm to 200nm.
6. The perovskite solar cell according to claim 1, characterized in that: The perovskite absorption layer is an ABX3 type perovskite light absorption layer.
7. The perovskite solar cell according to claim 6, characterized in that: The ABX3 type perovskite light absorbing layer is a FAPbI3 perovskite light absorbing layer.
8. The perovskite solar cell according to claim 1, characterized in that: The thickness of the perovskite light-absorbing layer ranges from 400 nm to 600 nm.
9. The perovskite solar cell according to any one of claims 1 to 8, characterized in that: The perovskite solar cell comprises from bottom to top at least a conductive substrate, an electron transport layer, the organic sulfonate buried interface modification layer, a perovskite light absorption layer, a hole transport layer and a back electrode.
